Answer:
s = 11.
Step-by-step explanation:
To find the value of 's', we can first use the Supplementary Angles theorem. If '12s' is the measure of the angle outside of the triangle, the angle inside the triangle must be equivalent to '180-12s'.
Since the sum of all of the angles of the triangle must be 180°, we can set up an equation to solve for 's':
180 = 45 + 10s - 23 + 180 - 12s (Subtract both sides by 180)
Simplify:
0= 45 + 10s - 23 - 12s (Subtract both sides by 45, and add 23 to both)
-22 = 10s - 12s
-22 = -2s (Divide both sides by -2)
s = 11.
PLZZ HURRY
q1)
Simplify. 6(5p^3 − 6p)
Answer:
30p^3−36p
Step-by-step explanation:
6(5p^3−6p)
=(6)(5p^3+−6p)
=(6)(5p^3)+(6)(−6p)
=30p3−36p
Answer:
30p^3−36pStep-by-step explanation:
6(5p^3−6p)
(6)(5p^3+−6p)
(6)(5p^3)+(6)(−6p)
=30p^3−36p
This is not copied i did the work!
WILL GIVE BRAINLIEST
Answer:
10/3
Step-by-step explanation:
6 length is 2 height.
So 10(6+4) length is 10/3 height
Answer:
x = 10/3
Step-by-step explanation:
These two triangles are similar by AA similarity, as they share angle A, and both have right angles.
Not we can set up a ratio:
6/(6+4) = 2/x
6/10 = 2/x
3/5 = 2/x
Multiply both sides by 5x,
3x = 10
Divide both sides by 3:
x = 10/3
For 20 points
Please Help it is due today and I I don't get how to find the height. I am a 7th grader and it is a 6th grade work for the whole class. I didn't even do this in 6th grade it is hard
Please Help
Answer:
The height of trapezoid is 7km.
Step-by-step explanation:
Given that the area of trapezoid formula is A = 1/2×(a+b)×h where a and b represents the length and h is the height. By substituing the values, you are able to find the height :
[tex]area = \frac{1}{2} \times (a + b) \times h[/tex]
Let a = 4km,
Let b = 8km,
Let area = 42km²,
[tex]42 = \frac{1}{2} \times (4 + 8) \times h[/tex]
[tex]42 = \frac{1}{2} \times 12 \times h[/tex]
[tex]42 = 6 \times h[/tex]
[tex]6h = 42[/tex]
[tex]h = 7 \: km[/tex]
Answer: 7km
Step-by-step explanation:
Please help me answer this question.
Answer: 5 miles
Step-by-step explanation:
Lucia surveyed the students in her class and made a dot plot of the results. What question could Lucia have asked?
Answer:
How many days do you exercise in a week?
Step-by-step explanation:
The topic is students' weekly exercise so the question has to be about that. also, there are up to 7 days worth of data and there a 7 days in a week. so she most likely asked the question, "How many days do you exercise in a week?".
PLEASE HELP WILL GIVE BRAINLIEST AND 20 POINTS
add these fractions and select the simplified answer
m+n/6mn + m-n/2mn
or
[tex]\frac{m+n}{6mn} + \frac{m-n}{2mn}[/tex]
Answer:
2m-n / 3mn
Step-by-step explanation:
combine the fractions by finding a common denominatorPlease help me answer this question
Two students are asked to go to the board to work
Answer:
Give us a actual equation mate
Step-by-step explanation:
Thomas has 4 blocks colored blue, red ,green and yellow. How many different ways can he combine them on a shelf?
The math question is attached below.
FOR 13+POINTS
Answer:
91.7
Step-by-step explanation:
V = π x r² x h
V = π x 2² x (8-0.7)
V = π x 4 x 7.3
V = 91.73
HELP IMPORTANT In one U.S. city, the taxi cost is $2 plus $0.50 per mile. If you are traveling from the airport, there is an additional charge of $6.00 for tolls. How far can you travel from the airport by taxi for $38.00?
Answer:
60 miles
Step-by-step explanation:
f(x) = 2 + 0,5 * m + 6
38 = 2 + 0,5 * m + 6
38 = 8 + 0,5 * m
30 = 0,5 * m
m = 60 miles
When the equation 2x+15−−−−−−√−x=0 is solved correctly, the solutions are x=−3 and x=5.
Which, if any, of the solutions are not valid?
A) The solution x=−3 is not valid.
B) The solution x=5 is not valid.
C) Neither solution is valid.
D) Both solutions are valid.
\frac{(2_1-4_{2}) ^{4} } {2}
I will give you brainliest
Answer:
I think the answer is 8
Step-by-step explanation:
Hi can I please get some help please thank you please please I need it WILL MARK AS BRAINLIEST !!!
Answer: D
Step-by-step explanation:
A and C are linear equations therefore we can eliminate them.
We are left betwen C and D.
C.
x²=25
x=5, x=-5
For C, we can eliminate because when you solve for x, you get 2 linear equations. You may see the x² and think it's linear, but when you solve it, you get 2 linear equations.
We are left with D. Even if you graph it and it doesn't look like a parabola or quadratic, it is still a quadratic equaiton. The 1/ makes it split both ways.
Which expression is equivalent to the given expression?
(12g^2h^7)(3g^-2h^-4)
Answer:
B
Step-by-step explanation:
(12g²h⁷)(3g⁻²h⁻⁴) = 12 * 3 * g²⁺⁽⁻²⁾ * h⁷⁺⁽⁻⁴⁾
= 36 * g⁰ * h³
= 36 * 1 * h³
= 36h³
Any variable or constant to the power of zero is 1
a⁰ = 1 ; 12⁰ = 1 ; (-5)⁰ = 1
Describe the graph of y+3x^2 and compare it with the graph of y=x^2
Answer:
y = 3x^2 is compressed by 3.
As y = x^2 is the parent graph, you can see how big a difference 3 makes.
Hope this helps!
(Red: y = 3x^2)
(Blue: y = x^2)
The transformation for the given function is vertical compression or stretch.
The given functions are y=3x² and y=x².
What is the function?Functions are the fundamental part of the calculus in mathematics. The functions are the special types of relations. A function in math is visualized as a rule, which gives a unique output for every input x.
The graph for the given functions can be determined as follows
To find the transformation, compare the expression to the parent function and check to see if there is a horizontal or vertical shift, reflection about the x-axis or y-axis, and if there is a vertical stretch.
Horizontal Shift: None
Vertical Shift: None
Reflection about the x-axis: None
Reflection about the y-axis: None
Vertical Compression or Stretch: Compressed
Therefore, the transformation for the given function is vertical compression or stretch.
To learn more about the function visit:
https://brainly.com/question/28303908.
#SPJ5
Which of the trigonometric expressions represent an inverse function?
Answer:
the second one:
tan-1(xdegree)
Step-by-step explanation:
2 Points
Choose the number below that represents the digit in the tens place of the
number 184
A. 8
B. 4
C. 1
D. 10
Slope of the line that passes through (2,1) and (8,4), please!
Answer:
Slope is 1/2
Step-by-step explanation:
Slope Formula: [tex]\frac{y_{1}-y_{2}}{x_{1}-x_{2}} \\[/tex]
Plug in points: [tex]\frac{4-1}{8-2} =\frac{3}{6}=\frac{1}{2}[/tex]
Please help! 19 points! Brainliest to best answer! Solve for the following equation step by step and justify your steps when using an exponential property. [tex]7x^4=\frac{7^2*7^3}{7^3^x}[/tex]
Answer:
ummm i dont know but try 16 35/21
Step-by-step explanation:
Answer: x^4 /7^3x-6
Step-by-step explanation:
7x^4 * 7^5 / 7^3x
7x^4 * 1 / 7^3x-5
Reduce expression with 7
x^4 * 1 / 7^3x-6
= x^4 / 7^3x-6
Add the polynomials.
(x2−11x+6)+(x2+5)
Answer:
[tex] \boxed{2 {x}^{2} - 11x + 11} [/tex]
Step-by-step explanation:
[tex] = > ( {x}^{2} - 11x + 6) + ( {x}^{2} + 5) \\ \\ = > {x}^{2} - 11x + 6 + {x}^{2} + 5 \\ \\ = > {x}^{2} + {x}^{2} - 11x + 6 + 5 \\ \\ = > 2 {x}^{2} - 11x + 11[/tex]
Answer:
2x^2 - 11x +11
Step-by-step explanation:
combine like terms
Find the sum of the integers from -6 to 57.
51
Step-by-step explanation:
57 + (-6)=51
since 6 is negative you subtract 6 from 57
Any one know this pls explain how u figured it out
Answer:
x=236
Step-by-step explanation:
44+80+x=360
x=solve it
Simplify the expression completely:
4x^2+2x-42/4x /(x-3)
Answer:
(x (8 x^2 - 20 x + -33))/(2 (x - 3))
Step-by-step explanation:
Simplify the following:
4 x^2 + 2 x - (42 x)/(4 (x - 3))
The gcd of 42 and 4 is 2, so 42/4 = (2×21)/(2×2) = 2/2×21/2 = 21/2:
4 x^2 + 2 x - x/(x - 3) 21/2
Put each term in 4 x^2 + 2 x - (21 x)/(2 (x - 3)) over the common denominator 2 (x - 3): 4 x^2 + 2 x - (21 x)/(2 (x - 3)) = (8 (x - 3) x^2)/(2 (x - 3)) + (4 (x - 3) x)/(2 (x - 3)) - (21 x)/(2 (x - 3)):
(8 x^2 (x - 3))/(2 (x - 3)) + (4 x (x - 3))/(2 (x - 3)) - (21 x)/(2 (x - 3))
(8 (x - 3) x^2)/(2 (x - 3)) + (4 (x - 3) x)/(2 (x - 3)) - (21 x)/(2 (x - 3)) = (8 (x - 3) x^2 + 4 (x - 3) x - 21 x)/(2 (x - 3)):
(8 x^2 (x - 3) + 4 x (x - 3) - 21 x)/(2 (x - 3))
Factor x out of 8 (x - 3) x^2 + 4 (x - 3) x - 21 x, resulting in x (8 (x - 3) x^(2 - 1) + 4 (x - 3) - 21):
(x (8 x^(2 - 1) (x - 3) + 4 (x - 3) - 21))/(2 (x - 3))
2 - 1 = 1:
(x (8 x (x - 3) + 4 (x - 3) - 21))/(2 (x - 3))
8 x (x - 3) = 8 x^2 - 24 x:
(x (8 x^2 - 24 x + 4 (x - 3) - 21))/(2 (x - 3))
4 (x - 3) = 4 x - 12:
(x (4 x - 12 + 8 x^2 - 24 x - 21))/(2 (x - 3))
Grouping like terms, 8 x^2 + 4 x - 24 x - 21 - 12 = 8 x^2 + (-24 x + 4 x) + (-12 - 21):
(x (8 x^2 + (-24 x + 4 x) + (-12 - 21)))/(2 (x - 3))
4 x - 24 x = -20 x:
(x (8 x^2 + -20 x + (-12 - 21)))/(2 (x - 3))
-12 - 21 = -33:
Answer: (x (8 x^2 - 20 x + -33))/(2 (x - 3))
Zeke goes to a skate shop with his friend Tristan. Tristan buys a helmet that costs $28.75. Zeke finds a helmet that is [tex]\frac{3}{5}[/tex] of the cost of Tristan's helmet. If Zeke gives the cashier a $20 bill, how much change will he receive.
Answer: $2.75
Step-by-step explanation:
Zeke's helmet cost 3/5 x 28.75 = 17.25
Change = 20 - 17.25 = 2.75
Answer:
2.75
Step-by-step explanation:
the math question is attached below
and please explain how you got the answer
Answer:
[tex]20\pi units^3[/tex]
Step-by-step explanation:
Answer:
V = 62.8 units³
Step-by-step explanation:
Once the area of a circle is:
[tex]A=\pi r^2[/tex]
The volume of a cylinder is:
[tex]V=\pi r^2 h[/tex]
where [tex]h[/tex] is the height of the cylinder.
Once, [tex]r=2 \text{ and } h=5[/tex]
[tex]V=3.14 \cdot 2^2 \cdot 5\\V=3.14 \cdot 20\\V=62.8 \text{ units cubed}[/tex]
What is the probability a King is chosen? Express your answer as a fraction, in simplest form.
A(1/52
B(1/13
C(1/4
D(4/13
Answer:
1/13
Step-by-step explanation:
In a deck of 52 cards, there are 4 kings
P(king) = number of kings / total cards
P (king) = 4/52
= 1/13
what is the difference between the greatest and least amount of juice? could you please tell me how to do it
Answer:
More juice.
Step-by-step explanation:
The difference between the greatest and least amount of juice is that there is more juice in one cup. If this is not the answer you were looking for, please let me know, and I am sorry for the inconvienience.
Simplify the following expression:
2x − 2y + 5z − 2x − y + 3z
x − 3y + 8z
2x − 2y + 8z
3y + 8z
−3y + 8z
Answer:
-3y+8z
Step-by-step explanation:
Here we want to combine all the like terms together to simplify the expression:
2x-2y+5z-2x-y+3z=\\ 2x-2x-2y-y+5z+3z=\\ -3y+8z
Answer:
a
Step-by-step explanation:
Ekene was curious if sample range was an unbiased estimator of population range. She placed ping pong balls
numbered from 0 to 32 in a drum and mixed them well. Note that the range of the population is 32.
She then took a random sample of 5 balls and calculated the range of the sample. She replaced the balls and
repeated this process for a total of 50 trials. Her results are summarized in the dotplot below, where each dot
represents the sample range from a sample of 5 balls.
.
ea
8
12
16
20
24
28
32
Sample range
Based on these results, does sample range appear to be a biased or unbiased estimator of population range?
Hint: The population range is 32.
Choose 1 answer:
Sample range appears to be a biased estimator since it consistently underestimated the population
Answer:
(a) Sample range appears to be a biased estimator since it consistently underestimated the population range.
Step-by-step explanation:
The sample ranges appear to be centered below 32
I got this right on Khan
In this exercise we have to use, in addition to the knowledge of statistics, the graph informed in the exercise in this way, we can say that:
Letter A
When we look at the graph, the maximum points are at 21 and 31, while the samples ranges appear to be centered below 32, that is we can say that the letter A is more appropietate.
See more about statistics at brainly.com/question/10951564